Some Results on Asymptotic Stability of Order α - Vu, Thi Thu Huong; Vu, Tuan (Ukrains’kyi Matematychnyi Zhurnal, 2005)
Quasi-equiasymptotic stability of order $α (α ∈ ℝ_{+} * )$ with respect to a part of variables is considered. Some sufficient conditions, a converse theorem, and a theorem on multistability are proved.